The Effect of Depth on Carrageenan Content in Kappaphycus alvarezii Culture in the Waters of Teluk Gerupuk - Aini, Kuratul; Cokrowati, Nunik; Affandi, Rangga Idris (Jurnal Biologi Tropis, 2025)
Kappaphycus alvarezii is a red seaweed commonly found in the Indo-Pacific region. Seaweed plays an important role in daily life due to its high nutritional value and its content of hydrocolloid compounds such as carrageenan, agar, and alginate. Carrageenan is categorized into three types: iota, kappa, and lambda. It is widely applied in various sectors including food, pharmaceuticals, and cosmetics. This study aimed to identify the optimal cultivation depth to maximize the carrageenan content in Kappaphycus alvarezii. The research employed an experimental method using different depth treatments over a cultivation period of 45 days. A completely randomized design (CRD) was applied, consisting of four treatments with three replications, resulting in a total of 12 experimental units. The treatments were as follows: P1 (0 cm depth), P2 (25 cm), P3 (50 cm), and P4 (75 cm). The research procedure included the construction of floating rafts, seedling preparation, tying of seedlings, planting, sampling, and harvesting. The best results were observed in treatment P1 (0 cm depth), which yielded the highest carrageenan content at 40%, the greatest absolute weight at 350 grams, and the highest specific growth rate at 5.90% per day.